Associations Between Physical Fitness, Objectively Measured Physical Activity and Academic Performance - Ðurić, Saša; Bogataj, Špela; Zovko, Vinko; Sember, Vedrana (Frontiers in Public Health, 2021)
Physical and psychological benefits of physical activity (PA) are widely acknowledged, while there is no abundant evidence about direct effects of physical activity on cognition. We recruited healthy adolescent girls, aged 11-12 years. Physical activity was measured with accelerometer ActiGraph GT3X for consecutive 5 days. Physical fitness was measured with 8 motoric tests and 3 anthropometry measures. Academic performance (AP) was assessed for 6 academic narrated school subjects. The results revealed that the girls were more physically active during the week and less at weekend (557 vs 516 counts/min). Physical education grade shows the highest overall correlations with the results of the physical fitness test battery (r = 0.53-0.95, p<0.01). Nevertheless, correlations surprisingly decrease for the combined daily PA (r = 0.45), especially the weekend PA (r = 0.28). Grade point average and physical fitness correlated moderately (r = 0.43-0.64), while they were moderate to high for physical activity (r = 0.59-0.87). Many questions arose after the completion of the present study and several new topics opened up, such as the question of how parental education affects the duration of PA and AP of the children and the influence of the place of residence AP of the children.